Ectopic Male Breast Cancer in Suprapubic Area That Relapsed with Hematogenous Metastasis - Byon, Jung Hee; An, Ae Ri; Shin, Jin Yong; Choi, Eun Jung (Journal of breast cancer, 2021)
Tough ectopic male breast cancer is extremely rare, non-axillary ectopic male breast cancer is even rare. To date, the natural course and prognosis of this disease are not fully understood. Consequently, the appropriate treatment for this disease has not been established. We report on a patient with ectopic male breast cancer in the suprapubic area that relapsed with hematogenous metastasis 3 years after complete surgical resection and adjuvant treatment despite an early diagnosis. This unusual case highlights the need for new prognostic factors such as genomic profiling to predict whether ectopic male breast cancer is aggressive and to guide on the duration between follow-ups and the appropriate method for conducting them.Tough ectopic male breast cancer is extremely rare, non-axillary ectopic male breast cancer is even rare. To date, the natural course and prognosis of this disease are not fully understood. Consequently, the appropriate treatment for this disease has not been established. We report on a patient with ectopic male breast cancer in the suprapubic area that relapsed with hematogenous metastasis 3 years after complete surgical resection and adjuvant treatment despite an early diagnosis. This unusual case highlights the need for new prognostic factors such as genomic profiling to predict whether ectopic male breast cancer is aggressive and to guide on the duration between follow-ups and the appropriate method for conducting them.